The degree of difficulties during performance of activities of daily living in patients with chronic obstructive pulmonary disease - Maňhalová, Jana; Kimmer, David; Schönbauerová, Andrea; Tóthová, Valérie (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
Introduction: The presenting paper deals with the degree of difficulties during the performance of activities of daily living (ADLs) in patients with chronic obstructive pulmonary disease (CHOPN). Aim: The aim of this paper is to present subjectively felt quality of life in the ill with CHOPN in the area of independence where we have focused on problems of ADLs performance. Methodology: The paper relates to the research grant project No. 120/2012/S, which is implemented under the financial support of the Grant Agency of the University of South Bohemia in České Budějovice and its title is “Reflection of Quality of Life in Nursing”. The research file was formed by 503 respondents with CHOPN from all over the Czech Republic from that 296 men (58.8%) and 207 women (41.2%). The standardized questionnaires WHOQOL-100 and SGRQ were used for data collection. The submitted paper presents only the results acquired through the questionnaire WHOQOL-100 in the Czech version which investigates subjectively the emotional quality of life, health and other life areas. The presented results go from the domain “independence”, where we have focused on the facet “ADLs”. Results: Pursuant to the acquired data, it was ascertained that almost 50% of the respondents perceive their ability to perform ADLs neutrally. Further it was ascertained that during performance of these activities approximately three quarters of respondents do not feel marked restrictions. Only less than 13% of the respondents are dissatisfied with their ability to perform ADLs. Discussion: According to our opinion the chronic ill patients are often even not aware of degree of symptoms which affect them because they have adapted to their disease to a certain degree. Conclusion: Although CHOPN is a treatable disease which can be preceded to the considerable degree, prognosis of this disease is not quite favourable because the disease is in progress all the time.
Míra obtíží při vykonávání každodenních činností u pacientů s chronickou obstrukční plicní nemocí
Keywords: ADLs; difficulties; patient; WHOQOL-100; quality of life; nursing; CHOPN; každodenní činnosti; obtíže; pacient; WHOQOL-100; kvalita života; ošetřovatelství